Harnessing virtues for educational success: introducing the Positive Development and Assessment Competencies Theory (PDAC) - Vazquez-Marin, Pedro; Curle, Samantha; Gil Ortega, Maria del Carmen; Medina-Gual, Luis; Sandoval-Hernández, Andrés (Frontiers in Education, 2025)
This study investigates the role of positive psychology virtues in predicting educational competencies 5th and 6th-grade students. The evidence-based benefits of fostering virtues in educational settings, including academic success, emotional resilience, ethical behavior and social integration, are well documented. This research further emphasizes the contribution of virtues to the formation of well-rounded individuals, prepared for lifelong learning and personal growth. Using a quantitative, correlational, cross-sectional design, data were collected from 993 students through validated questionnaires. Random forest logistic regression analysis identified six as significant predictors of perceived competencies, with Transcendence standing out as a particularly strong and consistent predictor across multiple competencies. These findings emphasize the profound impact of virtues on student development. The study also introduces the Positive Development and Assessment Competencies Theory (PDAC), which advocates for the integration of virtue-based interventions and character strengths into educational programs. PDAC aims to enhance the assessment of subjective competencies, improve educational interventions, and promote student wellbeing.